The Influence of pH on the Catalytic Capacity of Levodopa in the Electroreduction Processes of Zn2+ Ions - Jolanta Nieszporek; Tomasz Pańczyk (Molecules, 2025)
The aim of the study was to investigate the influence of L-DOPA—the gold standard in the treatment of Parkinson’s disease symptoms—on the electroreduction kinetics of Zn2+ ions. It was demonstrated that this effect depends not only on the concentration of the drug but also on the environment in which the process takes place. In the experimental part, cyclic voltammetry (CV), square wave voltammetry (SWV), direct current polarography (DC), and electrochemical impedance spectroscopy (EIS) were used. Based on the obtained results, it was determined that the analyzed electrode reaction, both in the absence and presence of L-DOPA, proceeded in two steps. The kinetic parameters of Zn2+ ion electroreduction indicated its quasi-reversible nature in solutions with both pH = 2.0 and pH = 6.0. The presence of the drug in the lower pH solution resulted in a slight slowing down of the electrode process, whereas in the pH = 6.0 solution, it led to a significant acceleration. In both low and high pH solutions, the first step was slower and determined the rate of the entire electrode process.